If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -3m + 1 = -7 Reorder the terms: 1 + m + -3m = -7 Combine like terms: m + -3m = -2m 1 + -2m = -7 Solving 1 + -2m = -7 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2m = -7 + -1 Combine like terms: 1 + -1 = 0 0 + -2m = -7 + -1 -2m = -7 + -1 Combine like terms: -7 + -1 = -8 -2m = -8 Divide each side by '-2'. m = 4 Simplifying m = 4
| 6(2x+4)+8x= | | 4b-1=3b+2 | | 4b-1=3b+3 | | 6(3x+5)-15= | | (35x+67y)+(46x-25y)= | | 3w-1=2(3w+7) | | 3x*9-23=77+2x | | 4x*3+29=84+x | | 67x=84-83+-1 | | 244x+672=1334 | | 2x=17.8 | | K^2=16 | | 7x*3+19-3x=57-2 | | 84x=0 | | 9x+24=60 | | 0.7x+4.2=11.2 | | 3x-17=45 | | 2x^3-5x^2-4x+5=0 | | 10X-X=99 | | Logw(x+1)=2 | | 5(x-2)=6(2x+1) | | 11=11x | | 15n-4+2n= | | -3*-1= | | 4x-(2x-3)=0 | | 5m-3-9m+4= | | 3x^2+9x+8=y | | 3x^2+9x+8=0 | | n^2=1 | | n^2=0 | | n^2+3*n+1=0 | | 5x+6x=18 |